Periodos críticos de competencia de las malezas en los cultivos de arroz y maíz. - CARPIO SUAREZ, GINGER MARIA (2023)
This investigative work consisted of compiling all the necessary information in different sources, of information on the cultivation of rice (Oryza sativa L) and corn (Zea mays L.), since it is very essential for the feeding of the national and world population, In addition, these two crops generate a very important economic income for farmers. In addition, it provides a source of work for the people who are in charge of cultivating it. It can be said that certain weeds serve to prevent soil erosion, in addition that some weeds serve as medicinal plants and for food purposes, since they recycle mineral nutrients from the soil, despite this there are several plants that are not arable and are called "undesirable" where the crop is different and for this reason they are considered weeds, because they are products of the alterations of the natural vegetation, since they constitute the most important economic component of the total pest complex, since they incorporate vertebrate insects, nematodes, and plant pathology. To avoid competition with the crop for light, water, nutrients and space, it is recommended to control weeds correctly, apply post-emergence herbicides in the rice crop (Oryza sativa, L) and in corn, in both planting stages, we must also evaluate the incidence that weeds have on crops and thus avoid economic losses to producers.